Global case studies/reports are really useful for learning Global Health? - Bhattacharya, Sudip; Singh, Amarjeet (Indian Journal of Community Health, 2017)
In medical sciences ,a case report means a comprehensive description of the symptoms ,signs, diagnosis , treatment, and follow-up of an individual patient. It may or may not contain a demographic profile of the patient, but generally depicts an unusual or novel manifestation. Case reports are basically professional chronicles that offer an important feedback on clinical practice guiding principle and offer an outline for early indicators of effectiveness, adverse events, and cost. They can be shared for scientific or educational purposes. A case report is usually considered as a type of an anecdotal evidence. Due to their inherentmethodological limitations, i.e. lack of statistical sampling, case reports are placed at the foot of the grading of clinical evidence. Yet, case reports do have genuinely valuable roles in clinical research and evidence based medicine. In precise, they have facilitated to recognize of new diseases i.e. Ebola, Zika etc. <p style="margin: 0in; margin-bottom: .0001pt; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">Clinical trial is much lengthier and resource consuming that a case report, so it is now gaining popularity among clinical researchers. In fact, there is a definite need to further popularize the concept of case reports.With the consonance of case reports, in clinical trials the concept of sample size calculation is rapidly changing. Such trials are labeled as “n-of-1 or single subject clinical trials.” It this trials, the researcher consider an individual patient as the sole unit of observation in a study. The final goal of this trial is to determine the optimal intervention for an individual patient by using objective driven criteria.Despite their clear appeal and extensive use in educational settings, n-of-1 trials have been used sparingly in medical settings. This is because that n-of-1 trials demand serious attention among the health research and clinical care communities and it is focused on individualized medicine. <p style="margin: 0in; margin-bottom: .0001pt; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">Across the globe people live in diverse circumstances. Their lifestyle, culture, health care scenario is different. Case studies/reports(CS/CR) can effectively illustrate these differences through description of experiences pertaining to a specific case. In medical sciences, it is a complete description of an individual patient starting from diagnosis of a disease to follow-up. It may or may not include a patient’s complete profile, but generally depicts an uncommon or novel manifestation. CRs are basically professional chronicles that offer an important feedback on treatment guiding principle and offer an outline for early indicators of usefulness, unnatural events and cost-effectiveness. These findings are usually disseminated for scientific or educational purposes. (1) <p style="margin: 0in; margin-bottom: .0001pt; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">Most clinical case reports are based on these topics: An unusual relation between diseases or signs, event during the treatment of a patient, results that highlights shed new light on a new mechanism of disease pathogenesis. It may be an antagonistic effect of drugs, uncommon findings of a common disease, exceptional healing approaches or an anatomical variation of human structures.